TINJAUAN KRIMINOLOGIS DALAM KASUS PELECEHAN SEKSUAL OLEH OKNUM ANGGOTA KEPOLISIAN PADA ANAK SAAT MENYELESAIKAN MASALAH TILANG (Studi Kasus di Kantor Satuan Lalu Lintas Kepolisian Resor Kota Kupang Kota) - Yusuf Alberto Gusman Hamburg; Orpa G. Manuain; Rudepel Petrus Leo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Sexual abuse of children committed by law enforcement officers constitutes an abuse of authority that not only violates criminal law but also undermines public trust in the police institution. This study aims to analyze the criminological factors contributing to child sexual abuse committed by police officers and to examine the measures undertaken to address such offenses. The research employed an empirical legal method using a criminological approach. Data were collected through interviews, literature review, and analysis of relevant legislation, and were analyzed qualitatively. The findings indicate that the crime is influenced by internal factors, including uncontrolled sexual impulses, offender rationalization, and abuse of power, as well as external factors such as unequal power relations, weak institutional supervision, situational opportunities, and the vulnerability of child victims. Countermeasures consist of pre-emptive, preventive, and repressive approaches, including strengthening professional ethics, enhancing internal supervision, implementing strict standard operating procedures, enforcing criminal and disciplinary sanctions, and providing legal protection and psychological recovery for victims. These integrated measures are expected to prevent future abuses of authority while ensuring effective legal protection for children.